Easing the burden of multi‐state genetic counseling licensure in the United States: Process, pitfalls, and possible solutions. Issue 1 (12th July 2021) - Tschirgi, Matthew L.; Owens, Kailey M.; Mackall, Mia S.; Allen, Jamie; Allen, Rachel
Abstract: State‐based genetic counseling licensure creates standardization, ensures high‐quality care, and supports the credentialing of genetic counselors (GCs) in the United States. However, it also has the unintended consequence of requiring substantial time and resources from genetic counselors who need to obtain licensure in multiple states. There is a wide range of variability among state licensure applications, required supporting documentation, verification processes, and cost—all of which are barriers for genetic counselors. New licensure laws are being passed on a regular basis, further complicating this process. Resources may be available to some genetic counselors such as employer reimbursement and administrative support; however, access to this support is not universal. This paper reviews the current condition of genetic counseling multi‐state licensure, including barriers, unique challenges, and possible solutions for increased efficiencies, based on the authors' experiences and examples found in other healthcare fields.